Catchment delineation and parameterization using gis technique for Kuantan River - Nur Aliah Aini, Jamaluddin (2018)
Kuantan City has a history of experiencing the flood since past decades. Due to the flood problem, the local authority has spent a lot of money in the flood mitigation work to reduce the impact of the flood on society. Kuantan River has been identified as one of the rivers that contributes flood problem. Heavy rainfall can cause the excess of runoff rise to the high water levels and cause the area to be flooded. Moreover, Kuantan has experienced a rapidly developed. The land use is changed to accommodate the demand for many purposes such as residential, industrial and agricultural purposes. Therefore, to realize changes of river basin and surface features, study the characteristics of the catchment is necessary. This study utilized satellite data (ASTERGDEM) to delineate and parameterize the catchment area of Kuantan River catchment using Geographical Information System (GIS). It was a process to determine the characteristics of catchment as the first step of flood mitigation project. Pre-processing of satellite data was carried out to improve the accuracy of elevation data. Catchment parameters such as area, slope, and basin centroid were extracted and these parameters is an important input for rainfall-runoff modeling for future studies. In addition, the result from this study was important to give initial information on characteristics of the catchment to the local authorities such as Department of Irrigation and Drainage.